Rome profile of a city, 312 - 1308 - Krautheimer, Richard 1897-1994 (Princeton Univ. Press, 2000)
Rome has long held an attraction as one of the world's great cultural, religious, and intellectual centers. In this classic study, surveying the city's life from Christian Antiquity through the Middle Ages, Richard Krautheimer focuses on monuments of art and architecture as they reflect the historical events, the ideological currents, and the meaning Rome held for its contemporaries. Lavishly illustrated, this book tells an intriguing story in which the heritage of antiquity intertwines with the living presence of Christianity. Written by one of the great art historians of our time, it offers a profile of the Eternal City unlike any drawn in the past or likely to be drawn in the future.